Dampak Eksternalitas Positif PT. Petrokimia Gresik Terhadap Masyarakat Dalam Perspektif Maqashid - Elfira Rizki Rahmadhani; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This study aims to determine the impact of the positive externalities resulting from the presence of Petrokimia Gresik Ltd. to the public about the industry. Positive externalities resulting from the existence of an industry in the surrounding community to support the increased revenue to achieve public welfare through employment and trade around the industry. The approach used in this study is a qualitative approach. The subjects of this study are Petrochemicals Ltd Dept. Public Relations Section Head, Section Head Petrokimia Gresik Ltd. CSR Dept., and communities around Petrokimia Gresik Ltd that provides the necessary information during the research process. Based on the results of this study indicate that the presence of Petrokimia Gresik Ltd has positive externalities impact on surrounding communities by improving living standards, income, infrastructure development,employment and prosperity.